CONTENT AND LANGUAGE INTEGRATED LEARNING IN RUSSIAN TECHNICAL UNIVERSITIES - T. V. Sidorenko; S. V. Rybushkina (Russian State Vocational Pedagogical University, 2017)
Introduction. The paper presents an overview of and reasons behind Content-Language Integrated Learning (CLIL). Nowadays, CLIL is clearly on its way to becoming an option - not yet an obligation - for higher education in the world. Against the background of internationalization and globalization perspectives, educational institutions around the globe face the need to create borderless education that entails the challenge of programme competitiveness and language acquisition. CLIL is considered as a driver for both. The efficacy of the approach made Russian educators look at its side taking into account the lack of «drag and drop» practices and the specificity of Russian university environment, including national specificity of the country in general.The aim of the article is to work out some recommendations for smooth implementation of CLIL in Russian higher education.Methodology and research methods. The methods involve system-based and comparative analysis, generalization and modeling.Results and scientific novelty. The existing theories and descriptors specifying CLIL approach are analysed; the review of CLIL implementation in higher education abroad is drawn up. The possibilities of inclusion of elements of CLIL approach in educational process of modern higher education institution for the purpose of improvement of language training of experts and a condition of internationalization of high school education in general are considered from the positions of national specifics of the Russian system of higher education, and also culturological, social, economic and political factors.Practical significance of the published material consists in suggestions and recommendations for improvement of university graduates' language training, which has to correspond ideally to the level sufficient for implementation of international professional activity. According to the authors, the requirement of such preparation should be recorded in educational standards as an indispensable condition of getting higher education.